HAPPY BIRTHDAY, YOU’RE FIRED! EFFECTS OF AN AGE-DEPENDENT MINIMUM WAGE ON YOUTH EMPLOYMENT FLOWS IN THE NETHERLANDS - KABÁTEK, JAN (Industrial & labor relations review, 2021)
The Dutch minimum wage for workers aged 15 to 23 is defined as a stepwise increasing function of a worker’s calendar age. Using Dutch administrative records, the author shows that the birthday discontinuities of age-dependent minimum wage rates affect both labor market entry (job accessions) and labor market exit (job separations) of minimum wage workers. The job separations spike in the three months that precede workers’ birthdays, suggesting that firms are dismissing workers whose costs are about to go up. The frequency of job accessions increases immediately after the birthdays and the increase is sustained throughout the following months. The resulting effect on employment levels is dynamic, with the employment rate being subject to an initial drop that is gradually compensated for by the higher rates of post-birthday labor market entry.